Manajemen Riayah Masjid Al-Hidayah Kelurahan Bandar Selamat Medan - Adriansyah, Ilham Budi; Haikal, Muhammad Fachran (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This research explores the Riayah Management of Al-Hidayah Mosque in Bandar Selamat Village, Medan, focusing on the understanding and obstacles in its maintenance. Through a descriptive qualitative approach using interviews, observations, and documentation, the results show that the mosque is progressing despite facing some challenges. The challenges include the lack of human resource development that is still in the revamping stage, the inconsistency of the mosque's SOP that causes unexpected negligence, limited funds for maintenance, and the lack of active participation from the congregation. A deeper understanding of mosque management, knowledge renewal, and active support from the congregation are needed to create a better mosque environment. Therefore, mosque administrators are advised to continue deepening their knowledge of relevant management concepts as well as maintaining existing working principles. Overall, this study makes an important contribution to the understanding of mosque management and highlights the need for continuous improvement in maintenance to enhance the welfare of Muslims.